The Urgency of Regulations Revision Related to Filing Bankruptcy and Postponing Debt Payment Obligations Amid the COVID-19 Pandemic - Nuriskia, Centia Sabrina; Novaliansyah, Ahmad Yoga (Universitas Negeri Semarang, 2021)
The purpose of this research is to analyze the requirements of bankruptcy regulations and postponement of debt payment obligations on the increase in bankruptcy filings and delays in debt payment obligations in the middle of the COVID-19 Pandemic. This research uses a normative juridical research method with a statutory approach and a conceptual approach that is supported by primary and secondary legal materials. The results of this research indicate that the increase in filing for bankrBankruptcydelays in paying debt obligations at the Commercial Court is due to unclear rules regarding filing for bankrBankruptcyecially the requirements in filing for bank bankruptcy do not specify the amount of debt that can be filed for bankrBankruptcyre is a need for consideration in making and stipulating bankruptcy arrangements, both in the Draft Civil Procedure Code and the Bankruptcy Law and Suspension of Debt Payment Obligations, especially on issues: the amount of debtor debt, simple evidence, creditors holding guarantees in bankrBankruptcyminal confiscation in bankrBankruptcyker wage rating, bankruptcy estate settlement, and position of the arbitration award in bankruptcy cases.